Exploring the Use of Traditional Medicines, Natural Health Products and Conventional Medicines: Development and Testing of the New Zealand 'All-Medicines' Questionnaire - E Lyn Lee; Jeff Harrison; Joanne Barnes (Adis, Springer Healthcare, 2023)
Abstract Introduction Traditional, complementary and alternative medicine (TCAM) are popular healthcare choices among consumers globally. The latest national data on the use of TCAM practitioners in New Zealand (NZ) were collected over a decade ago. Robust data on the use of natural health products (NHPs) and TCAM practices alongside conventional medicines are not yet available in NZ. Objectives This study aimed to develop and test a bespoke questionnaire (All-MedsNZ) that included comprehensive data collection elements exploring NHPs' and conventional medicines' use. Methods This was a questionnaire design study involving expert panel feedback, and engagement with TCAM users, in the development process. This work comprised questionnaire development (stage 1) followed by a questionnaire-testing study (stage 2). The questionnaire was developed on the basis of literature review findings and the research team's expertise. The questionnaire content was then validated by an expert panel comprising practitioners in TCAM and conventional medicine. Then, a two-phase study was utilised to test the questionnaire. Phase 1 involved participants (NHP users) completing the web-based questionnaire and providing feedback by answering probing questions added throughout the questionnaire to evaluate users' comprehension of the questions and to identify issues with the questionnaire. In phase 2, selected participants were interviewed online to gain in-depth insights into issues identified in phase one. Based on these findings, the questionnaire was revised. Results The expert panel (n = 9) confirmed the questionnaire had high face and content validity; most original questions were retained. In the questionnaire-testing study, 95 and 27 participants completed the phase 1 and 2 studies, respectively. Most questions achieved a high response rate of ≥ 90%, and participants had no major issues understanding and answering the questionnaire. Problematic questions were those relating to providing product barcodes and photographs, and information on product costs. Most of the NHPs data entered by participants included the brand/generic name, manufacturer/company name, main ingredient(s) and dose form. Generally, these NHP-related data were of acceptable quality. However, information on the main ingredient(s) of products entered by participants was less satisfactory: approximately one-third of the 143 NHPs recorded in the study had the main ingredient(s) missing or incorrectly stated. Interviews with participants reiterated the issues identified in the phase 1 study. The low response rates for some of the questions were partly due to participants' unpreparedness (i.e. not having NHPs/medicines on hand) to complete the questionnaire. In addition, a lack of clarity for the term 'natural health practitioner' led to confusion among some participants. Conclusion Overall, no major design-, method- or questionnaire-related issues were identified in this development and testing work. The questionnaire demonstrated adequate face and content validity and acceptability among participants. The data collected were reasonably complete and of sufficient quality for analysis. Future studies should pilot the revised All-MedsNZ questionnaire with a larger, nationally representative sample to ascertain its feasibility and utility.